(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
Personalized learning has gained prominence as a learner-centered approach that adapts goals, pathways, pacing, and supports to individual needs while sustaining high expectations. This article traces the historical development of personalized learning and examines its theoretical roots in John Dewey’s learner-centered pragmatism, Lev Vygotsky’s sociocultural theory and zone of proximal development, and Carl Rogers’ humanistic, person-centered education. Building on these foundations, the paper explains why personalized learning is expanding in contemporary schooling: learner diversity, competency-oriented curricula, digital learning ecosystems, and renewed emphasis on agency and lifelong learning. The article then outlines practical methods for implementation in English language teaching, including differentiated instruction, mastery-based learning, blended and flipped models, station rotation, project-based learning, learning contracts, formative assessment cycles, and portfolio-based reflection. Finally, it synthesizes major pedagogical challenges that frequently appear during implementation—role transition for teachers, classroom management of multiple pathways, assessment alignment, equity and access, workload and time constraints, and responsible use of learning data—and proposes design principles to mitigate these risks.